Formulation, Optimization and Evaluation of Gastro-retentive Raft Forming Tablets of Atenolol for the Treatment of Hypertension - Yadav, Vaibhav; Sharma, Ajay; Khanam, Toshiba (Journal of Neonatal Surgery, 2025)
The present study aimed to develop and evaluate raft-forming controlled-release tablets of Atenolol using a floating drug delivery system to enhance gastric retention and sustain drug release. Formulations were prepared by the direct compression method using sodium alginate, sodium bicarbonate, and HPMC K15M as key excipients, with microcrystalline cellulose as a binder, talc as a diluent, and magnesium stearate as a lubricant. Precompression studies confirmed that the powder blends possessed good flow properties, while post-compression evaluations demonstrated satisfactory hardness, friability, weight uniformity, thickness, and drug content. In vitro buoyancy studies revealed that the combination of sodium bicarbonate and sodium alginate significantly influenced the floating lag time, ensuring prolonged gastric residence. Dissolution studies showed that the optimized formulation, F3, exhibited a controlled drug release over 12 hours, highlighting the role of HPMC K15M in modulating release kinetics. Raft strength measurements confirmed the mechanical stability of the gel, and preliminary stability studies indicated formulation robustness under accelerated conditions. Overall, these findings suggest that the optimized raft-forming tablets of Atenolol have potential for sustained therapeutic effects, improved patient compliance, and enhanced management of hypertension and related conditions...